2021
DOI: 10.1002/ags3.12456
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Glasgow prognostic score for short‐term surgical outcomes: A nationwide survey using the Japanese National Clinical Database

Abstract: Aim Preoperative inflammation‐based Glasgow prognostic score (GPS) is a useful tool for predicting long‐term prognosis in cancer patients. However, its association with postoperative short‐term outcomes remains unknown. The aim of this study is to investigate the association between GPS and postoperative morbidity and mortality among patients undergoing surgery for various gastrointestinal malignancies. Methods Using the Japanese National Clinical Database, we analyzed the records of 312 357 patients with gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“… 41 The Glasgow prognostic score was shown to be strongly correlated with postoperative outcomes. 42 Moreover, the mortalities after right hemicolectomy or pancreatoduodenectomy were not affected by day of the week. 43 , 44 In addition, in emergency surgery for acute diffuse peritonitis, antithrombotic drug usage was associated with a slight increase of intraoperative blood loss, which was thought to have little effect on clinical practice.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 41 The Glasgow prognostic score was shown to be strongly correlated with postoperative outcomes. 42 Moreover, the mortalities after right hemicolectomy or pancreatoduodenectomy were not affected by day of the week. 43 , 44 In addition, in emergency surgery for acute diffuse peritonitis, antithrombotic drug usage was associated with a slight increase of intraoperative blood loss, which was thought to have little effect on clinical practice.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to the other issues of postoperative mortality and morbidity rates in the NCD, the impact of reconstruction route on postoperative morbidity after esophagectomy was reported 41 . The Glasgow prognostic score was shown to be strongly correlated with postoperative outcomes 42 . Moreover, the mortalities after right hemicolectomy or pancreatoduodenectomy were not affected by day of the week 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…This study also analyzed systemic factors reportedly associated with postoperative complications, such as the BMI, 31 platelet/lymphocyte ratio, 32 neutrophil/lymphocyte ratio, 33 lymphocyte/monocyte ratio, 34 CRP/albumin ratio, 35 prognostic nutrition index, 36 prognostic index, 37 and GPS 38 . None were associated with postoperative complications, but both patients with a GPS of 1 had complications.…”
Section: Discussionmentioning
confidence: 99%
“…None were associated with postoperative complications, but both patients with a GPS of 1 had complications. Hiramatsu et al 38 found that patients with GPS 1 and 2 were significantly more likely to have postoperative complications than patients with GPS 0 in various surgeries. Although there were no significant differences in this study, these inflammatory and nutritional factors should be considered preoperatively, and if the risk of complications is high, the treatment should be more carefully considered to avoid postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative CRP values have been included in a number of observational studies aimed at predicting postoperative risk of morbidity with preoperative laboratory examinations [47,50], evaluating the risk of postoperative infective morbidity across a number of surgical specialities. A preoperative risk score has been developed and validated that relies on preoperative measures of serum CRP and albumin, called the Modified Glasgow Prognostic Score (mGPS) [79]. In this score, patients with preoperative CRP values >10 mg/L are deemed at increased risk of postoperative infective morbidity.…”
Section: Certaintyofevidencementioning
confidence: 99%